The Implementation of Establishing Marine Protected Area: Lessons Learned From Raja Ampat to Achieve Sustainable Fishery - Sri Wartini (PROGRAM STUDI MAGISTER ILMU HUKUM FAKULTAS HUKUM UNIVERSITAS DIPONEGORO SEMARANG, 2020)
Raja Ampat has one of the world’s richest coral reef, because it is located in the heart of the coral triangle. However, due to human activities, such as overfishing, shipping as well as climate change has caused serious impacts to the existence of the coral reef and its habitats. As the member of the United Nations Law of the Sea Convention and the Biodiversity Convention, Indonesia has obligation to establish Marine Protected Areas (MPAs). The research aims to analyze comprehensively the implementation of establishing the MPA in Indonesia based on international and national law perspective and to examine whether the existence of the MPA in Raja Ampat can be used as a model to develop MPA in other area to achieve sustainable fishery. This study is a normative juridical research by applying conceptual and statutory approaches. The result of the research finds that the establishing of MPA in Raja Ampat has been successfully achieved sustainable Fishery as part of sustainable development. However, there are some challenges that have to be addressed, such as lack of monitoring in the MPAs due to the limitation of the budget as well as the illegal unreported and unregulated fishing conducted by the people outside indigenous community Thus, it is necessary to conduct monitoring cooperation among the MPAs.